Infra-Hisian atrioventricular conduction disorder in a patient with treated acromegaly - Bareta Sironi, Brenda; Malavazzi Rodrigues, Rafaela; Borges Machado, Marcos (Brazilian Journal of Case Reports, 2022)
Severe atrioventricular (AV) conduction disorder in acromegalic patients is limited to rare case reports with pacemaker implantation. This is a report of a 49-years-old female patient with cure criteria for acromegaly for 24 years and a history of syncope and lipothymia. The electrocardiogram showed a first-degree AV block. 24-hour Holter recorded Mobitz I second-degree AV block. The bundle of His electrogram showed prolongation of the HV interval (conduction time between the location where the His bundle potential is recorded and the beginning of ventricular activation). Thus, an artificial pacemaker was implanted with symptomatic improvement. The objective is to highlight atrioventricular conduction disorders in acromegalic patients and cardiological monitoring importance.